Highly variable removal of pathogens, antibiotic resistance genes, conventional fecal indicators and human-associated fecal source markers in a pilot-scale stormwater biofilter operated under realistic stormflow conditions. (1st July 2022) - Rugh, Megyn B.; Grant, Stanley B.; Hung, Wei-Cheng; Jay, Jennifer A.; Parker, Emily A.; Feraud, Marina; Li, Dong; Avasarala, Sumant; Holden, Patricia A.; Liu, Haizhou; Rippy, Megan A.; Werfhorst, Laurie C. Van De; et al.
Highlights: Field-scale biofilter evaluated under realistic, transient flow conditions. Normalization of microbial analyte removal to breakthrough of the conservative tracer bromide. Biofilter significantly reduced 14 of 17 microbial analytes. No significant reduction in concentration for two fecal source markers. Abstract: Green stormwater infrastructure systems, such as biofilters, provide many water quality and other environmental benefits, but their ability to remove human pathogens and antibiotic resistance genes (ARGs) from stormwater runoff is not well documented. In this study, a field scale biofilter in Southern California (USA) was simultaneously evaluated for the breakthrough of a conservative tracer (bromide), conventional fecal indicators, bacterial and viral human-associated fecal source markers (HF183, crAssphage, and PMMoV), ARGs, and bacterial and viral pathogens. When challenged with a 50:50 mixture of untreated sewage and stormwater (to mimic highly contaminated storm flow) the biofilter significantly removed ( p < 0.05) 14 of 17 microbial markers and ARGsin descending order of concentration reduction: erm B (2.5 log(base 10) reduction) > Salmonella (2.3) > adenovirus (1.9) > coliphage (1.5) > crAssphage (1.2) > E. coli (1.0) ∼ 16S rRNA genes (1.0) ∼ fecal coliform (1.0) ∼ intl 1 (1.0) > Enterococcus (0.9) ∼ MRSA (0.9) ∼ sul 1 (0.9) > PMMoV (0.7) > Entero1A (0.5). No significant removal was observed for GenBac3, Campylobacter, and HF183. From the bromide data, we infer that 0.5 log-units of attenuation can be attributed to the dilution of incoming stormwater with water stored in the biofilter; removal above this threshold is presumably associated with non-conservative processes, such as physicochemical filtration, die-off, and predation. Our study documents high variability (>100-fold) in the removal of different microbial contaminants and ARGs by a field-scale stormwater biofilter operated under transient flow and raises further questions about the utility of human-associated fecal source markers as surrogates for pathogen removal. Graphical abstract: Image, graphical abstract